Implementation of The Ethnographic Approach in Multicultural Education - Ainii, Lathifah Qurrotu; Amalia, Mega; Pratiwi, Niken Ayu; Maryam, Siti; Edora, E; Kurnia, Ira Restu (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to describe the implementation of the ethnographic approach in multicultural education at the elementary school level. This approach is used as strategy to bring student closer to cultural diversity through experiental learning. The research was conducted in several elementary school in the Cikarang area using a descriptive qualitative method. Data were collected through observation, interviews, and document analysis. The findings show that the ethnographic approach encourages students to understand and appreciate cultural differences through direct interaction with the social environment. Multicultural values developed during the learning process include tolerance, curiosity toward other cultures, and pride in each student’s own cultural identity. However, the implementation of this approach faces challenges, such as a lack of teacher training in ethnographic methods and limited time for its integration into classroom activities. Therefore, this study recommends specialized training for teachers and the systematic integration of the ethnographic approach into the curriculum to strengthen multicultural education at the elementary level.